1=12-4g+7+7g

Simple and best practice solution for 1=12-4g+7+7g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1=12-4g+7+7g equation:


Simplifying
1 = 12 + -4g + 7 + 7g

Reorder the terms:
1 = 12 + 7 + -4g + 7g

Combine like terms: 12 + 7 = 19
1 = 19 + -4g + 7g

Combine like terms: -4g + 7g = 3g
1 = 19 + 3g

Solving
1 = 19 + 3g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-3g' to each side of the equation.
1 + -3g = 19 + 3g + -3g

Combine like terms: 3g + -3g = 0
1 + -3g = 19 + 0
1 + -3g = 19

Add '-1' to each side of the equation.
1 + -1 + -3g = 19 + -1

Combine like terms: 1 + -1 = 0
0 + -3g = 19 + -1
-3g = 19 + -1

Combine like terms: 19 + -1 = 18
-3g = 18

Divide each side by '-3'.
g = -6

Simplifying
g = -6

See similar equations:

| 3(4m+3)=4 | | -2(3p+7)=-16 | | (24m^-2n^4/16m^3n^-5) | | 4g-17+2g-3=4 | | Logx(8)=-1 | | 5n+4n=18 | | 7-9w-11=10 | | 13=7+3-7y | | 9(x-16)=3(x+8) | | x-v+2=w+2 | | 7x+6-6x=7 | | 16-7w=-5 | | (n-2)180=22340 | | 13+2-3x=9 | | -4x+8x=-4 | | 123=-2+5x | | 4x^2-15x-22=0 | | -15+8r=-3 | | 9=7+p-9 | | 17=3-4p | | 12w-13=-85 | | 4x+7-5=-2 | | 2x=-3x+38 | | 2k^2+6k+4.5=0 | | 5a^7/2b^5c | | X^2+y^2+20x-10y+4=0 | | 225x^6-81y^10=0 | | 4x^2+19x-8=0 | | 484=28x+36y | | J=mug | | X^2+y^2-8x-24y=9 | | 2/3x-41/2=8 |

Equations solver categories